The impact of food policy on food insecurity in developing countries - Abdul Manap, Nur Marina; Sidique, Shaufique Fahmi; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
Food insecurity is one of the major issues in the developing countries which are debate seriously. The affected countries suffer from hunger and undernourishment, due to their incapability to provide sufficient nutritious food. Insufficiency on nutritious food is cause by several factors such as climate change, food crisis and natural disaster problem. The united States agency International development (uSaId) food policy highlights food availability, accessibility and utilization as three major dimensions in achieving food security. The proxy for food insecurity is based on three important variables namely prevalence of food Inadequacy (pfI), prevalence of undernourishment (pou) and Depth of Deficit (DFD). This paper examines the impact of these dimensions on food insecurity in selected developing countries, using the country fixed effect model. The findings of this study show that an increase in food production, food import, purchasing power parity and water improvement are found to have positive impacts on improving food insecurity.